2020
DOI: 10.3390/children7050039
|View full text |Cite
|
Sign up to set email alerts
|

Grief and Bereavement in Parents After the Death of a Child in Low- and Middle-Income Countries

Abstract: While great strides have been made in improving childhood mortality, millions of children die each year with significant health-related suffering. More than 98% of these children live in low- and middle-income countries (LMICs). Efforts have been made to increase access to pediatric palliative care (PPC) services to address this suffering in LMICs through policy measures, educational initiatives, and access to essential medicines. However, a core component of high-quality PPC that has been relatively neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…While qualitative research does not strive for generalisability (Braun & Clarke, 2013), it is important to note that the experiences of this small group of men may not be representative of all men who experience TOPFA. There is a need for future research to focus particularly on under‐represented populations including rural and remote men, culturally and linguistically diverse men, men who experience relationship breakdown following infant loss, men from low and middle‐income countries, and gay, trans/masculine and non‐binary people (McNeil et al, 2020; Riggs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While qualitative research does not strive for generalisability (Braun & Clarke, 2013), it is important to note that the experiences of this small group of men may not be representative of all men who experience TOPFA. There is a need for future research to focus particularly on under‐represented populations including rural and remote men, culturally and linguistically diverse men, men who experience relationship breakdown following infant loss, men from low and middle‐income countries, and gay, trans/masculine and non‐binary people (McNeil et al, 2020; Riggs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these deaths occur before the focal individual’s birth: upward of 10% of women report being born to a bereaved mother, with estimates ranging from 2–4% (Colombia, South Africa) to 25% (Niger). Prior work shows that the death of a child is a major life course event that fundamentally shapes women’s lives [ 78 ]; future research that explicitly studies how bereavement affects parents, and their subsequent children is sorely needed. The particularly high levels of youth born to bereaved mothers in several African countries affected by conflict and war demonstrate the specific need for such research in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…life course event that fundamentally shapes women's lives [78]; future research that explicitly studies how bereavement affects parents, and their subsequent children is sorely needed. The particularly high levels of youth born to bereaved mothers in several African countries affected by conflict and war demonstrate the specific need for such research in these settings.…”
Section: Plos Onementioning
confidence: 99%
“…38 It has been reported that women can face stigma and blame in child deaths. 39 The power imbalance and gendered interviewer-interviewee dynamics present in this study may therefore have influenced mothers' emotional stress and willingness to freely discuss their child's death. These dynamics may also be present when multiple respondents were interviewed together, for example, a husband and wife.…”
Section: (Meo 4)mentioning
confidence: 94%